The Role of Interpersonal Communication in the Work Environment from Islamic Perspective - Budi Budi; Bunga Br Lubis; Yuli Amelia (Edumaspul: Jurnal Pendidikan, 2023)
In the process of running an organization smoothly, various forms of skills are needed so that a company can develop well and smoothly. These skills must be possessed by every employee. If there are new employees, old employees must be able to teach them about the culture that exists in a company. Apart from that, new employees must also be able to adapt to the new company environment. The aim of making this journal is to find out the role of interpersonal communication in the work environment from an Islamic perspective. Interpersonal communication within an organizational scope such as the work environment requires a process to achieve the desired performance. Effective interpersonal communication will provide information quickly and also provide clearer ideas which is important in the work environment.